2020
DOI: 10.1108/fs-10-2019-0090
|View full text |Cite
|
Sign up to set email alerts
|

A decision support system for road freight transportation route selection with new fuzzy numbers

Abstract: Purpose This study aims to propose a framework for designing appropriate triangular fuzzy numbers in a fuzzy analytic hierarchy process (FAHP) for selecting a road freight transport route and investigate the appropriate fuzzy numbers determined from a reliable consensus among participating experts based on the Delphi method. Design/methodology/approach The fundamental nine-point scale was investigated and separated into nonfuzzy intervals for importance assessment. A total of 17 individual experts participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…Participants are allowed to change their initial responses. Each participant's responses in each round are collected and presented by combining the mean and standard deviation 24 . The Delphi method has been widely used in various fields 24 .…”
Section: Research Methods and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants are allowed to change their initial responses. Each participant's responses in each round are collected and presented by combining the mean and standard deviation 24 . The Delphi method has been widely used in various fields 24 .…”
Section: Research Methods and Materialsmentioning
confidence: 99%
“…Each participant's responses in each round are collected and presented by combining the mean and standard deviation 24 . The Delphi method has been widely used in various fields 24 . Considering the unique characteristics of the Delphi method, this study utilized the technique to identify factors influencing process safety culture.…”
Section: Research Methods and Materialsmentioning
confidence: 99%
“…The ZOGP model as an effective MCDM approach for solving independent or conflicting objectives is an extension of linear programming and is used to rank an alternative based on total deviations in ascending order, where all decision variables are either zero or one; zero is non‐selection, while one is selection (Meethom & Koohathongsumrit, 2020). This approach can be divided into many types: simple, interactive weighted, extended, Chebyshev, reference point, compromise programming, and lexicographic methods (Özcan et al, 2017).…”
Section: Principles Of the Relevant Methodsmentioning
confidence: 99%
“…zero is non-selection, while one is selection (Meethom & Koohathongsumrit, 2020). This approach can be divided into many types: simple, interactive weighted, extended, Chebyshev, reference point, compromise programming, and lexicographic methods (Özcan et al, 2017).…”
Section: Zero-one Goal Programmingmentioning
confidence: 99%
“…According to the previous foresight studies on the issues related to food, they mostly use the data from trends, driving forces, hindsight, emerging issues and insights generated by experts (Garnett et al , 2016; Bourgeois and Sette, 2017; Brooks and Place, 2019). Delphi survey was one of the useful technique to use for gathering and synthesizing expert opinions for stronger key possibility (Meethom and Koohathongsumrit, 2020; Wehrle et al , 2022). The study of Antonelli M. et al shown the use of Delphi survey to gather the key trends and perspectives of the Mediterranean agri-food system (Antonelli et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%